Analysis of genetic diversity and correlation in sugarcane (Saccharum spp. L) clones in North-West zone of Uttar Pradesh - Kumar, Devendra; Nirmal; Ram Meena, Laxman; K. Meena, Lalit; Lal Meena, Amrit; KJ, Raghavendra; Bhowmik, Arpan (Journal of Sugarcane Research, 2023)
In order to assess the genetic diversity and character association, nine early maturing sugarcane clones were studied in 2015-16 and 2016-17 crop seasons under inorganic environment in summer planting regime. The results of the experiment revealed that variety CoPk 05191 had greater genetic distance from CoS 03251 (239.401), CoLk 11201 (227.923) and UP 05125 (201.355), medium genetic distance was between Co 98014 and Co 11201 (224. 618), Co 98014 and UP 05125 (179.927), and Co 98014 and CoS 03251 (178.029). The hybridization between the aforesaid combinations of clone scan produce heterotic and transgressive genotypes with higher cane and sugar yield. The cane yield showed strong positive and highly signiﬁcant correlation with cane height (r=0.948**), single cane weight (r=0.817**), number of millable canes (r=0.748**), and green top yield (r=0.653**). Being highly correlated with cane yield, the characters like cane height, cane weight, NMC and green top weight need special focus while making selection for higher cane and sugar yield.